Nutritional Status and Determinants of Malnutrition in Children under Three Years of Age in Nghean, Vietnam - Hien, Nguyen Ngoc; Hoa, Nguyen Ngoc (Pakistan Journal of Nutrition, 2009)
To assess the nutritional status and to determine potential risk factors of malnutrition in children under 3 years of age in Nghean, Vietnam. The study carried out in November 2007, a total of 383 child/mother pairs were selected by using a 2-stage cluster sampling methodology. A structured questionnaire was administered to mothers in their home settings. Anthropometric measurement was defined as being underweight (weight for age), wasting (weight for height) and stunting (height for age) on the basis of reference data from the National Center for Health Statistics (NCHS) / World Health Organization (WHO). Logistic regression analysis was used to into account the hierarchical relationships between potential determinants of malnutrition. The mean Z-score for weight-for-age was -1.51 (95% CI -1.64, -1.38), for height-for-age was -1.51 (95% CI -1.65, -1.37) and for weight-for-height was -0.63 (95% CI -0.78, -0.48). Of the children, 103 (27.7.8%) were underweight, 135 (36.3%) were stunted and 38 (10.2%) were wasted. Region of residence, ethnic, mother’s occupation, household size, mother’s BMI, number of children in family, weight at birth, time of initiation of breast-feeding and duration of exclusive breast-feeding were found to be significantly related to malnutrition. The findings of this study indicates that malnutrition is still an important problem among children under three years of age in Nghean, Vietnam. Socio-economic, environmental factors and feeding practices are significant risk factors for malnutrition among under-three.